Now - Portis, Antoinette (Roaring Brook Press, 2017)
"This is my favorite cloud ... because it's the one I am watching. This is my favorite tree ... because it's the one where I'm swinging. This is my favorite tooth ... because it's the one that is missing." Follow a little girl as she takes you on a tour through all of her favorite things, from the holes she digs to the hugs she gives.